2017
DOI: 10.1038/srep44128
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of SGLT2 inhibitors for adjunctive treatment of type 1 diabetes: a systematic review and meta-analysis

Abstract: To assess the efficacy and safety of the SGLT-2 inhibitors as adjunct therapy to insulin in T1DM, clinical trials indexed in PubMed, Cochrane Library, EMbase from inception through April 5, 2016. A meta-analysis was conducted on trials of SGLT-2 inhibitors in patients with T1DM on insulin therapy using RevMan 5.3 software. Of the 371 articles identified, ten met eligibility criteria. Seven clinical trials including four randomized controlled trials and 581 patients were included. Compared with the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 42 publications
(147 reference statements)
6
80
1
2
Order By: Relevance
“…Compared with the previous reports, the present analysis not only presented so far the largest sample size and more extracted parameters, but also provided a more detailed subgroup analysis for high, medium and low doses on the safety and efficacy of SGLT2 inhibitors.…”
Section: Introductionmentioning
confidence: 91%
“…Compared with the previous reports, the present analysis not only presented so far the largest sample size and more extracted parameters, but also provided a more detailed subgroup analysis for high, medium and low doses on the safety and efficacy of SGLT2 inhibitors.…”
Section: Introductionmentioning
confidence: 91%
“…17 The limitations of the present study include the exploratory nature and study design; from day 3 to day 13, patients were administered ipragliflozin but not on an inpatient basis, nor were they monitored for safety under the same conditions as they had been in the hospitalization period (from day −2 to day 3, and day 13 to day 15). Therefore, caution is advised during this period of treatment, as it is possible the initial increase in hypoglycaemic events could have been a result of an insufficient reduction in insulin dose.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems however with SGLT2i use in this arena is that it may cause euglycaemic diabetic ketoacidosis (DKA) in both T1DM and T2DM when used in in combination with insulin (12).The method by which this occurs is suggested that as SGLT2i reduce blood glucose levels they reduce insulin secretion which in turns leads to a reciprocal increase in free fatty acid concentration and therefore ketone production in the liver. In addition SGLT2i's have been found within alpha cells on the pancreas and as such have been found to increase glucagon production which can mediate carnitine palmitoyl transferase-I activity which is a potent inducer of free fatty acid oxidation further increasing ketone production (14).…”
Section: Resultsmentioning
confidence: 99%
“…Complicating this matter further is the fact that there is a paucity of studies looking at SGLT2 inhibitor use in T1DM and they often utilise a small number of patients during a limited study period. As such the conclusions made from them are of limited use; as such therapy must be used for life (12). That being said it has been demonstrated that SGLT2 inhibitor use within T1DM can lead to decreased insulin requirements of up to 16%, this is particularly of benefit in the young who often omit insulin for fear of its anabolic effects (7).…”
Section: Resultsmentioning
confidence: 99%